Making trade sustainable impact assessment more relevant to trade negotiations - Voituriez, Tancrède... [et al.] (2006)
Analyzes the difficulties in achieving mutually beneficial multilateral trade agreements. Proposes a set of five motives to depart from free trade in trade negotiations, ranging from the protectionist-bias argument down to arguments for universal exceptions from trade liberalisation. Such arguments pave the way of past negotiations success and failures, from the 1947 Havana Charter to the Doha Development Cycle.